The Case of ‘To Know Is To Hear’ in Bahasa Indonesia - Besse Puspitha Syarif; Leini Nadira Rambe; Panji Tanashur (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study explores the relationship between sensory experience and cognition in Bahasa Indonesia through the conceptual metaphor “TO KNOW IS TO HEAR.” Although cognitive semantic studies have examined conceptual metaphors in many languages, research on Indonesian cognitive semantics, particularly sensory-based cognition, remains limited. Drawing on Natural Semantic Metalanguage (NSM) and Conceptual Metaphor Theory (CMT), this study investigates how Indonesian speakers conceptualize knowledge, understanding, and information through hearing-related expressions. The data consist of lexical items associated with cognition, including dengar (‘hear’), tahu (‘know’), and paham (‘understand’), as well as figurative expressions such as kabar angin (‘wind news’), kabar burung (‘bird news’), desas-desus (‘rumours’), menyampaikan ilmu (‘to convey knowledge’), and menuntut ilmu (‘to pursue knowledge’). Data were collected from Indonesian dictionaries, the Indonesian Corpus, and native-speaker intuition. The analysis combines dictionary examination, NSM explications, and metaphor analysis based on source and target domains. The findings indicate a close conceptual association between hearing and knowing in Bahasa Indonesia. Hearing functions not only as a sensory activity but also as a means of acquiring information, forming knowledge, and developing understanding. This study provides preliminary evidence for the conceptual metaphor TO KNOW IS TO HEAR in Bahasa Indonesia.